2008
DOI: 10.1097/mao.0b013e318182780d
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on a New Highly Porous Hydroxyapatite Matrix for Obliterating Open Mastoid Cavities

Abstract: Our results confirm the favorable qualities of the new ceramic reported in association with current maxillofacial literature. Conventional HA granules used for mastoid obliteration to date often showed problems with prolonged inflammatory reactions and, finally, extrusions. In contrast to those ceramics, the new material seems to induce more osteoneogenesis and undergoes early resorption probably due to its high porosity. Overall, it is similar to the bovine bone substance tested on the opposite ear in each an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…The density of the calcium phosphate matrix amounts to 0.5-0.7 g/cm 3 with a porosity of 60-80% (Gauthier et al 1998;Gerber et al 2000). Promising results in earlier animal and clinical studies were reported (Henkel et al 2004(Henkel et al , 2006Punke et al 2008Punke et al , 2009. The hydroxyapatite particles of NHA2 have a flat shape with an average diameter of 18 nm.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The density of the calcium phosphate matrix amounts to 0.5-0.7 g/cm 3 with a porosity of 60-80% (Gauthier et al 1998;Gerber et al 2000). Promising results in earlier animal and clinical studies were reported (Henkel et al 2004(Henkel et al , 2006Punke et al 2008Punke et al , 2009. The hydroxyapatite particles of NHA2 have a flat shape with an average diameter of 18 nm.…”
mentioning
confidence: 92%
“…, ; Punke et al. , ). The hydroxyapatite particles of NHA2 have a flat shape with an average diameter of 18 nm.…”
mentioning
confidence: 99%
“…After Zö llner and colleagues reported obliteration of the mastoid air cell with porous tricalcium phosphate ceramic, there were several reports about mastoid obliteration using glass ionomer cement, demineralized bone matrix, bioactive glass ceramic particles, and hydroxyapatite [6][7][8][9][10][11][12][13][14][15][23][24][25][26][27][28][29]. Among them, a calcium phosphate material has been widely used for bone replacement because of its good biocompatibility and osteoconductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically bone, autologous fat, cartilage and several local flaps are used to obliterate the mastoid cavity [1][2][3][4][5]. Some alloplastic materials such as hydroxyapatite and demineralized bone, have been used to fill the bony cavity defect [6][7][8][9][10][11][12][13][14][15]. However, some autologous materials or flaps can be dissolved over time and other alloplastic materials may not to be suitable to use because of their appearances and possibility for a foreign body reaction [3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, signs of angiogenesis could be observed (Abshagen et al 2009). Vascularization as well as osteoneogenesis after implantation of NanoBone ® was observed using guinea pigs (Punke et al 2008). Our own group could establish a FE model of remodelling processes occurring in a bone area provided with bone graft substitutes .…”
Section: Composites With Different Chemical Phasesmentioning
confidence: 99%